The nucleus accumbens in monkeys (Macaca fascicularis): I. The organization of behaviour. - Stern, C; Passingham, R (1994)
A behavioural comparison was made between six unoperated control monkeys and six monkeys which received bilateral ibotenic acid lesions of the nucleus accumbens. Two of the control monkeys were subsequently given bilateral lesions of the anterior cingulate and medial frontal cortex (areas 24, 25 and 32) and were retested on the behavioural tasks. The NA lesioned monkeys, but not the anterior cingulate lesioned monkeys, were significantly impaired on a hoarding task in which they were required to remove 18 peanuts from their shells and store them in their cheek pouches. These same monkeys were not impaired when the nuts were presented without shells. Evidence is provided which suggests that this deficit is not motivational or due to gross motor impairments. A second task in which the animals were required to search through four boxes to retrieve food revealed a decrease in the tendency for the NA and cingulate lesioned animals to use an organized pattern of searching. Both groups were found to return to a previously opened box more often than controls. However, neither group showed signs of perseverative behaviour. Data from a ten-box version of this task suggest that these return errors were not due to a decrease in working memory. Together these studies suggest that both the NA and the anterior cingulate cortex contribute to the ability to organize behaviour temporally and spatially.